Electricity pricing and market power: Evidence from Germany - Matthias Janssen; Magnus Wobben (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2008)
The aim of this paper is to develop a methodology for measuring the exercise of potential market power in liberalized electricity markets. We therefore investigate producer behavior in the context of electricity pricing with respect to fundamental time-dependent marginal cost (TMC), i.e. CO2- and fuel cost. In doing so, we do not - in contrast to most current approaches to market power investigation - rely on an estimate of the entire generation cost, which inevitably suffers from the lack of appropriate available data. Applying an analytical model of a day-ahead electricity market, we derive work-on rates, which provide information about the impact of TMC variations on electricity prices in the market constellations of perfect competition, quasi-monopoly and monopoly. Comparing these model-based work-on rates with actual work-on rates, estimated by an adjusted first-differences regression model of German power prices on the cost for hard coal, natural gas and emission allowances, we find evidence of the exercise of market power in the period 2006 to 2008. However, our results reveal that German market competitiveness increases marginally. We confirm our results by simulating a TMC-driven diffusion model of futures power prices estimated by maximum-likelihood.
Keywords: 330